Phytochemical screening, antimicrobial, anti-inflammatory and anti-cancerous activities of ethanol and hexane extracts of Urochloa ramosa - Singh, Abhijith M; N D, Rekha; Udayashankar, Arakere C; Sumana, K (Plant Science Today, 2022)
Urochloa ramosa is known for its environmental benefits such as stabilization and reclamation of polluted soils, in agriculture to control root-knot nematodes infecting crops, in medicine to treat cardiovascular diseases, duodenal ulcer, hyperglycemia, nephritis and snake bites. Qualitative analyses of phytochemicals in ethanol and hexane extracts were performed by standard methods. In vitro anti-microbial assay was performed against gram positive bacteria viz., Bacillus subtilis and Staphylococcus aureus, Gram negative bacteria viz., Pseudomonas aeruginosa and Escherichia coli and fungus Candida albicans by disc diffusion method. Hexane extract of Urochloa ramosa was found to be 70% effective against Candida albicans indicating potent antifungal property. In vitro anti-inflammatory activity was performed by albumin denaturation assay, proteinase inhibition activity assay and membrane stabilization assay using various concentrations of extracts with Aspirin and Diclofenac sodium as standard. Heat induced protein denaturation was considerably prevented by ethanol and hexane extract at concentrations between 200-500 µg/ml resulting in 60 and 62% inhibition respectively. Heat induced haemolysis of erythrocyte was remarkably inhibited (59 and 68 % respectively) at concentration of 500 µg/ml. 62 and 65 % Hypotonicity induced haemolysis was also inhibited between concentration of 300-500 µg/ml in both extracts respectively. Inhibition of formation of new blood vessels by Chorioallantoic membrane (CAM) assay proved anti-angiogenic effects of extracts. Purification, characterization and structural elucidation of bioactive molecules present in ethanol and hexane extracts are needed to be explored further for assessment of better biological activites than crude extract.